Mature Cystic Teratoma of Pancreas - Gill, Meenu; Kaur, Navneet; Dahiya, Mahak; Nityasha; Gupta, Veena; Jain, Promil; Singh, Sunita (Annals of Pathology and Laboratory Medicine, 2025)
Mature cystic teratoma (MCT) of the pancreas is an extremely rare benign tumor. We report a case of a mature cystic teratoma of the pancreas confirmed on histopathology in a 41-year-old male. Ultrasonography, computed tomography, and MRCP revealed evidence of a large cystic lesion at the head of the pancreas. The entire mass was excised. Microscopic examination revealed the diagnosis of benign mature cystic teratoma (dermoid cyst). Complete surgical resection of the cyst is necessary for definitive treatment.